História do sindicato dos professores de São Paulo (SINPRO-SP) em tempos de conflitos sociais e expansão do ensino privado (1975-1985) - Vicente, Hélida Balardini Lança (2019)
The research analyzed the performance of the Teacher Union from São Paulo (SINPRO-SP) during the last ten years at the civil-military dictatorship in the country (1975-1985), the redemocratization process was under construction and encountered political and economic obstacles for its achievement, forged on intense social conflicts with fundamental participation of the working class organized then. We endeavored to understand the participation of the teacher representative entity from private education network in São Paulo capital city in this important chapter of Brazilian history, confirming the understanding that the trajectory of a trade union organization has much to tell us about the context in which it is inserted, making possible the expansion of written pages about Brazilian education history during the dictatorship. The adopted theoretical frame of reference, Marxist inspiration, aimed at situating the teacher as an education worker, reminding us to analyze their union actions as a necessary task for us to have an expanded comprehension about the specificities of teaching activities, their relationships with the meanderings of educational policies and the way in which it attempted to intervene in the historical period of the so-called Brazilian democratic transition. Based on significant documentary fortunes, the performed analysis concerned not only to measure the dimension of the actions from the entity management board that remains worried in legitimizing the category corporatist purposes, as well as with the practices of those teachers who worked in the union opposition, engaged in the accomplishment of political actions and aligned with more general issues from the working class in Brazil.